Seroprevalence of Nipah Virus Infection in Peninsular Malaysia - Yong, Ming Yen; Lee, Soo Ching; Ngui, Romano; Lim, Yvonne Ai Lian; Phipps, Maude E.; Chang, Li Yen (Oxford University Press, 2020)
Nipah virus (NiV) outbreak occurred in Malaysia in 1998. The natural host reservoir for NiV is Pteropus bats, which are commonly found throughout Malaysia. Humans become infected when NiV spills over from the reservoir species. In this study, NiV serosurveillance in Peninsular Malaysia, particularly among the indigenous population, was performed. The collected samples were tested for presence of NiV antibodies using a comparative indirect enzyme-linked immunosorbent assay based on the recombinant NiV nucleocapsid (rNiV-N) protein. We found that 10.73% of the participants recruited in this study had antibodies against rNiV-N, suggesting possible exposure to NiV. © The Author(s) 2020. Published by Oxford University Press for the Infectious Diseases Society of America. All rights reserved. For permissions, e-mail: journals.permissions@oup.com.